1939
DOI: 10.1042/bj0330240
|View full text |Cite
|
Sign up to set email alerts
|

Studies in the biochemistry of micro-organisms

Abstract: THE following metabolic products, present in the metabolism solution of Penicillium griseo-fulvum Dierckx when this mould is grown under different cultural conditions and on different culture solutions, have been isolated in this laboratory: 6-hydroxy-2-methylbenzoic acid [Anslow & Raistrick, 1931], 2:5-dihydroxybenzoic acid (gentisic acid), fumaric acid and mannitol [Raistrick & Simonart, 1933] and fulvic acid, C14H1208, a yellow crystalline substance of at present undetermined molecular constitution [Oxfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

1959
1959
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(62 citation statements)
references
References 3 publications
0
62
0
Order By: Relevance
“…Interestingly, one of the oldest antifungals discovered in 1939, Griseofulvin, inhibits the cell cycle (Oxford et al, 1939). To elucidate the physiological changes of the fungal cells induced by DMHF, we performed flow cytometric analysis for cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one of the oldest antifungals discovered in 1939, Griseofulvin, inhibits the cell cycle (Oxford et al, 1939). To elucidate the physiological changes of the fungal cells induced by DMHF, we performed flow cytometric analysis for cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the cell cycle is of particular interest as a source of targets for drug development. 21) To elucidate the physiological changes of the fungal cells induced by I3C, we performed a flow cytometric analysis for cell cycle. The results showed that I3C arrested the cell cycle at the G 2 /M phase in C. albicans (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is a metabolic product of penicillium griseofulvin [2] and is chemically known as chloro-7-dimethoxy-4,6-oxo-3-benzo(b)dihydro-2-3, furane-2, spiro-4 methoxy-3 methyl-5 cyclohexene-2 one-1 . It gets deposited in keratin precursor cells, which become resistant to the invasion of dermatophytes.…”
Section: Introductionmentioning
confidence: 99%